ANALYSIS OF PROJECT COMMUNICATION FACTORS ON THE LEVEL OF PROJECT SUCCESS IN TEBO DISTRICT - Azman, Azman; Zaitul, Zaitul; Utama, Wahyudi P. (Rang Teknik Journal, 2025)
This research aims to identify communication factors that influence the success of construction projects in Tebo Regency, as well as determine the dominant factors that influence the success of these projects. The research method used was a field survey with data collection through questionnaires to parties involved in construction projects in Tebo Regency. The data obtained was analyzed using regression analysis to assess the influence of communication factors on project success. The research results show that the Communication Skills and Competency (KKK) factors have a positive and significant influence on project success, while the Information and Communication Technology (ICT), Communication Management Plan (RMK), and Teamwork (KJT) factors have a greater influence. low and insignificant.  The implication of this research is that parties involved in construction projects in Tebo Regency need to pay attention to and improve communication skills, both verbal and written, as well as effective use of information and communication technology. This can improve project implementation and achieve better results.